Immobilization and intracellular delivery of circular proteins by modifying a genetically incorporated unnatural amino acid - Bi, Xiaobao (2020)
Backbone-cyclic proteins are of great scientific and therapeutic interest owing to their higher stability over their linear counterparts. Modification of such cyclic proteins at a selected site would further enhance their versatility. Here we report a chemoenzymatic strategy to engineer site-selectively modified cyclic proteins by combining butelase-mediated macrocyclization with the genetic code expansion methodology. Using this strategy, we prepared a cyclic protein which was modified with biotin or a cell-penetrating peptide at a genetically incorporated noncanonical amino acid, making the cyclization-stabilized protein further amenable for site-specific immobilization and intracellular delivery. Our results point to a new avenue to engineering novel cyclic proteins with improved physicochemical and pharmacological properties for potential applications in biotechnology and medicine.